Corporate Sustainability Disclosure: A Leather Industry Perspective - Oluwaseyi Omoloso; William R. Wise; Kathleen Mortimer; Luai Jraisat (Ital Publication, 2020)
This study aims to identify and compare the key social, economic and environmental sustainability practices in the leather industry. Content analysis was used to analyse extracted sustainability information from either the website, annual report, sustainability report or corporate social responsibility report of six leather-related companies. Review of existing literature assisted in categorising different practices under social, economic and environmental sustainability, while an identification of patterns among practices followed. Findings reveal that companies are observing a good practice of either dedicating a section of their website to revealing their sustainability activities or utilising their sustainability reports or annual reports. Energy efficiency, waste management and reduction of greenhouse gases emission were the most occurring environmental sustainability practices. Health and safety occurred as the dominant social sustainability practice, while economic sustainability practices have not been well defined, providing an opportunity for future research. The study provides a useful resource for managers and companies in the leather supply chain to learn from brands that have been embarking on sustainability efforts and assist them to a better understanding of the concept, in readiness for strategy formulation, implementation and reporting.